2016
DOI: 10.1007/s10865-016-9774-2
|View full text |Cite
|
Sign up to set email alerts
|

The MEssaging for Diabetes (MED) intervention improves short-term medication adherence among low-income adults with type 2 diabetes

Abstract: Adults with type 2 diabetes (T2DM) and low socioeconomic status (SES) have high rates of medication nonadherence, and, in turn, suboptimal glycemic control (hemoglobin A1c [HbA1c]). We tested the initial efficacy of a short message service (SMS) text messaging and interactive voice response (IVR) intervention to promote adherence among this high-risk group. Eighty low SES, diverse adults with T2DM used the MEssaging for Diabetes (MED) SMS/IVR intervention for three months. We used a pre-post single group desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 23 publications
0
47
0
5
Order By: Relevance
“…Research that registered unsatisfactory results adopted in its intervention a period with a mean of three months. (4)(5)(6)9,10,12,(17)(18)(19)24,26,29,31,32) This is probably due to the short interval between measurements and the delay in compliance with selfcare practices. (33) Thus, in order to obtain expressive results, it is possible to estimate as the ideal time interval for the performance of the SMS interventions of eight to 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research that registered unsatisfactory results adopted in its intervention a period with a mean of three months. (4)(5)(6)9,10,12,(17)(18)(19)24,26,29,31,32) This is probably due to the short interval between measurements and the delay in compliance with selfcare practices. (33) Thus, in order to obtain expressive results, it is possible to estimate as the ideal time interval for the performance of the SMS interventions of eight to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be observed that a higher frequency of sending personalized messages and individual sending to each user contributed to the achievement of significant results. (5,9,20,22) Nelson LA., et al (2016) (31) "It is important that you take your medications for diabetes as prescribed. Doing this can help you live longer"; "If you have trouble remembering to take your medications for diabetes, try linking them to other activities you do every day"; "Everyone needs someone to talk about their diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of adults with type 2 diabetes, Phillips and colleagues tested behavioral initiation and maintenance factors derived from the CSM as correlates of adherence to medication and physical activity regimens. Additional studies in type 2 diabetes populations are also published in this issue: one examined dyadic data regarding various types of patient and spouse stressors as they relate to dietary and exercise adherence through mediating pathways involving depression symptoms and diabetesspecific self-efficacy (Anderson et al, 2016); another evaluated the efficacy of a text messaging/interactive voice response intervention on adherence and glycemic control in a sample of low-income adults with type 2 diabetes (Nelson et al, 2016); and one tested a number of constructs of modified social learning theory in relation to diabetes selfmanagement behaviors among type 2 diabetes patients on insulin regimens (Nugent & Wallston, 2016).…”
mentioning
confidence: 99%
“…It cannot be simply assumed that theoretical models applied in more traditional intervention settings ''transfer'' to such contexts. Two papers in the present issue are examples of theory-based mHealth interventions (i.e., Levine et al, 2016;Nelson et al, 2016).…”
mentioning
confidence: 99%